2021
DOI: 10.3389/fcimb.2020.608020
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Major Recurring Campylobacter jejuni Lineages in Luxembourg Using Four Core or Whole Genome Sequencing Typing Schemes

Abstract: Campylobacter jejuni is the leading cause of bacterial gastroenteritis, which has motivated the monitoring of genetic profiles circulating in Luxembourg since 13 years. From our integrated surveillance using a genotyping strategy based on an extended MLST scheme including gyrA and porA markers, an unexpected endemic pattern was discovered in the temporal distribution of genotypes. We aimed to test the hypothesis of stable lineages occurrence by implementing whole genome sequencing (WGS) associated with compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 91 publications
2
44
0
Order By: Relevance
“…While cgMLST is the reference method for the surveillance of Campylobacter spp., the combination of mass spectrometry and artificial intelligence may be a suitable tool to make a pre-selection of what need to be sequenced. Indeed, it has been shown recently that genetic lineages were frequently identified in human infection over-time in Luxembourg [19]. Using the same lineage isolates of Nennig et al (2021), we pushed the study at the clone level, confirmed by three cgMLST schemes and by comparing the pangenome (wgMLST).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…While cgMLST is the reference method for the surveillance of Campylobacter spp., the combination of mass spectrometry and artificial intelligence may be a suitable tool to make a pre-selection of what need to be sequenced. Indeed, it has been shown recently that genetic lineages were frequently identified in human infection over-time in Luxembourg [19]. Using the same lineage isolates of Nennig et al (2021), we pushed the study at the clone level, confirmed by three cgMLST schemes and by comparing the pangenome (wgMLST).…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, it has been shown recently that genetic lineages were frequently identified in human infection over-time in Luxembourg [19]. Using the same lineage isolates of Nennig et al (2021), we pushed the study at the clone level, confirmed by three cgMLST schemes and by comparing the pangenome (wgMLST). Eleven specific MALDI-TOF profiles have been linked to specific lineages identified over-time in Luxembourg.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Because the core genome contained only conserved genes and was relatively small in this elucidation here, this might lead to different phylogenetic relationships between them. In addition, other studies have also tried to distinguish the closely related C. jejuni genomes based on the core or whole-genome sequencing type schemes and found that some clinical strain genomes are more stable than others for over a decade ( Cody et al, 2013 ; Nennig et al, 2021 ). It is known that C. jejuni has a high genetic diversity with very few repeat sequences and virtually no inserted or phage-associated sequence in the genome ( Parkhill et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%